Aqueous extracts of Duranta repens (Verbenaceae) as an alternative to control tea red spider mite, Oligonychus coffeae (Acari: Tetranychidae). (16th March 2016) - Roy, Somnath; Muraleedharan, Narayanannair; Handique, Gautam; Rahman, Azizur; Barua, Archita
Abstract: We evaluated an aqueous extract of Duranta repens L. in the laboratory against the tea red spider mite, Oligonychus coffeae Nietner, to determine its effect on adult mortality, viability of eggs, oviposition deterrence and repellent properties. We also evaluated the same extract in the field to determine its effect on mite populations. The direct spray method was used in the laboratory at concentrations of 2, 4, 6, 8 and 10 g/l. Mortality of O. coffeae was dependent on both concentration and time after application. Deposition of eggs by adult mites on treated leaf surfaces decreased and the viability of eggs was also reduced. Its bioefficacy was comparable to that of the commonly used commercial neem oil formulation (azadirachtin 0.03EC). In addition, different concentrations of the aqueous extract of D. repens also exhibited repellent properties against adult mites. In the field, the application of the aqueous extract of D. repens reduced the mite population and its bioefficacy was comparable to that of the synthetic pesticide Propargite 57 EC. No phytotoxic effect was observed when tea bushes were sprayed with different concentrations of D. repens . Tea samples were taint free. Treatment of plants with the extract did not affect the quality (appearance of liquor, flavour, taint and taste) of made tea. Availability and distribution of this plant in and around tea growing areas of Assam, along with its processing, and the possibility of including D. repens extracts in the current IPM programme are discussed.